Comparison of Cytokine Profile between Indonesian Thin-Tailed and Merino Sheep during A Primary Infection with Fasciola gigantica - Wiedosari, Ening; Piedrafita, David (Jurnal Veteriner; Vol 13 No 1 (2012), 2012)
The aim of this study was to investigate the expression of cytokines profiles interferon-? (IFN-?),interleukin-5 (IL-5) and IL-10 in Rasciola gigantica resistant Indonesian thin-tailed (ITT) sheep comparedto susceptible merino sheep infected with Fasciola gigantica. A total of ten ITT and merino sheep wererandomly allocated into infected (n=5) and control (n=5) groups, sheep were infected with 250 viablemetacercariae of F. gigantica. The cytokines were determined by isolated mRNA from hepatic lymph nodeby semi-quantitative RT-PCR (Reverse Trancriptase -Polymerase Chain Reaction). The result showedITT sheep produced significantly higher IL-5 and 10 ( P<0,05 ) than merino sheep, while ITT sheepproduced less IFN-? ( P<0,05) than merino sheep at 10 weeks post infection. It could be concluded thatmerino sheep tend to develop T type 1 cells, while the ITT sheep tend to develop T type 2 cells whicheffectively killed F. gigantica.
Keywords: Fasciola gigantica; Indonesian thin-tailed sheep; merino sheep; IL-5; IL-10; IFN-?